The Economic Synthesis - Day, Clive; Paul, M. Eden (Quarterly Journal of Economics, 1915)
Journal Article The Economic Synthesis Get access Clive Day Clive Day Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 29, Issue 2, February 1915, Pages 401–409, https://doi.org/10.2307/1884967 Published: 01 February 1915